Membangun Karier Adaptif: Peran Keterampilan, Dukungan Teman, dan Efikasi Diri Keputusan Karier Siswa SMKN 1 Bendo Magetan: Building an Adaptive Career: The Role of Skills, Peer Support, and Self-Efficacy in Students' Career Decisions at SMKN 1 Bendo Magetan - Razan Ihtifazhuddan; Lilik Anifah; I Gusti Putu Asto Buditjahjanto (ITScience (Information Technology and Science), 2024)
The low interest and ability of SMKN 1 Bendo Magetan students in